(untitled) (Progressive Agriculture, 2017)
The purpose of this study was to analyze the socio-economic structure of water buffalo farming at some selected coastal areas of Bhola district of Bangladesh. Data were collected from the 35 small and large farms by surveying during the period January to March, 2015. The study revealed that buffalo rearing was mostly practiced by middle (30-45yrs) and old (>45yrs) aged farmers than young farmers (<30yrs). Majority (45.71%) of the buffalo farmers were educated, have no organized housing facilities for sheltering and depend on locally available roughages and tree leaves to fed buffaloes. The average lactation length was found 228 days andmilk yield was 2.1 litres/ buffalo/ days. The Gross Margin and Net farm profitability per dairy buffalo per lactation year over cash cost and non-cash cost were stood at Tk. 55866.65 & Tk. 51127.89 and Tk.44954.65 & Tk. 40435.39 for Herd size-1 and Herd size-2, respectively that indicates rearing of small- scale dairy buffaloes is highly profitable at coastal belt areas in Bhola District. The average Benefit Cost Ratio (BCR) was accounted for 1:7.51 and 1:3.11, respectively over cash and total cost basis considering both herds. Finding of this study indicates that buffalo rearing is highly profitable in the coastal areas of Bangladesh and a crucial pathway for poverty alleviation. Progressive Agriculture 27 (4): 502-510, 2016